EFEKTIFITAS PEMBERIAN TUNJANGAN SERTIFIKASI GURU TERHADAP KINERJA GURU IPA DAN PRESTASI BELAJAR IPA SISWA SMP/MTS DI JAYAPURA - Widinugroho, Agung; Modouw, James (Jurnal Ilmu Pendidikan Indonesia, 2016)
This study aims to: (1). To determine the relationship between the administration of the Benefit Teacher Certification Teacher Performance IPA SMP I MTs in Jayapura, (2). To determine the relationship between the administration of the Benefit Teacher Certification Achievement IPA SMP I MTs in Jayapura, (3). To determine the interaction between granting benefits to improving the Teacher Certification Teacher Performance IPA SMP I MTs and Learning Achievement IPA SMP I MTs in Jayapura, (4). To determine the effectiveness of Teacher Certification allowances for science teachers to improve their performance, (5). To determine the effectiveness of Teacher Certification allowances for science teachers to improve science learning achievement ill school, (6). To determine whether there is a difference in performance between the Master Teacher Certification Allowance recipients who have not been certified by the Master, (7). To determine whether there is a difference between the Teacher Achievement IPA Allowance recipients with Master Teacher Certification Certification. The results showed that: The relationship between teacher certification allowance with a science teacher performance SMP I MTs in Jayapura showed fairly strong correlation (r = 0.459), with the students learning achievement IPA strong enough correlation (r = 0.458), there is a fairly strong interaction between administration teacher certification benefits with improved performance science teachers SMP I MTs and learning achievement IPA SMP I MTs in the city of Jayapura, the effectiveness of teacher certification allowances on teacher performance IPA SMP I MTs in Jayapura quite effective while the effectiveness of teacher certification allowances for science learning achievement of students SMP I MTs quite effective, there is a difference ill performance between a science teacher with a teacher certification annuitant science teacher who has not been certified and there is no difference between the students learning achievement IPA beneficiaries science teacher certification with the science teacher who has not been certified. Keywords: Teacher Certification Benefits, Performance Teacher, Student Achievement